Dose Timing of Aminoglycosides in Hemodialysis Patients: A Pharmacology View. Issue 3 (12th January 2016) - Eschenauer, Gregory A.; Lam, Simon W.; Mueller, Bruce A.
Abstract: Aminoglycosides for patients undergoing intermittent hemodialysis (IHD) have traditionally been dosed at half the normal dose administered at the end of a hemodialysis session. Several investigations have suggested that administering higher doses preceding or with the initiation of dialysis would more readily optimize pharmacodynamic parameters. However, the selection of an optimal aminoglycoside dosing strategy in patients receiving IHD is complex and requires consideration of numerous factors, precluding a singular approach. By reviewing aminoglycoside pharmacokinetics, pharmacodynamics, risks for toxicity and resistance development, and practical considerations, we derive indication‐ and setting‐ specific recommendations. We identify some areas (definitive therapy of gram‐negative infections in patients receiving predictable hemodialysis sessions, for example) where dosing preceding or with the initiation of dialysis is optimal and feasible, and others (gram‐positive synergy, unstable patients with poor/unpredictable vascular access) where postdialysis dosing remains preferred. Finally, given the dearth of data exploring the pharmacodynamics and clinical outcomes of IHD patients receiving aminoglycoside therapy, we identify several key questions in need of investigation.